Development of an Integrated Web and Mobile-Based MSME Information System Using a User-Centered Design Approach - Alfarizqy, Dimas Anugrah Putra; Hidayat, Ahmad Tri (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This research focuses on the development of an integrated information system designed to promote and market the products of Micro, Small, and Medium Enterprises (MSMEs) by employing a User-Centered Design (UCD) methodology. The developed system encompasses a web-based platform for MSME agency administrators and a complementary mobile application for end consumers. The research methodology adhered to the four established phases of UCD: planning, design, development, and evaluation. The outcome of this process is a fully-featured system comprising a comprehensive product catalog, an integrated payment gateway supporting QRIS, e-wallet, and virtual account transactions, a shopping cart, a wishlist functionality, a product review and rating system, and real-time order tracking. A rigorous usability evaluation conducted using the System Usability Scale (SUS) yielded an impressive score of 85.2, which falls within the ""excellent"" acceptability range. The findings demonstrate that the system is highly effective in enhancing the visibility of MSME products and provides a secure and convenient platform for facilitating digital transactions for consumers.